Linking Accounting Information and Internal Controls to Sustainable Performance: Evidence on the Mediating Role of Management Control Systems - Sinarasri, Andwiani; Murniningsih, Rochiyati (Jurnal Analisis Bisnis Ekonomi, 2024)
This study examines the influence of the Internal Control System (ICS), Accounting Information System (AIS), and Management Control System (MCS) on Sustainability Performance among 88 Islamic Microfinance Institutions (IMFIs) in Central Java, Indonesia. Employing Smart PLS for data analysis, the findings reveal that: (1) the ICS exerts a significant effect on the MCS, with the MCS mediating the relationship between ICS and sustainability performance; and (2) the AIS does not significantly affect the MCS, nor does the MCS mediate the relationship between AIS and sustainability performance. The key theoretical contribution lies in highlighting the mediating role of MCS in translating ICS functions as internal control mechanisms into improved sustainability outcomes. Practically, the findings enrich the management accounting literature, offering insights for enhancing the design and application of MCS to support sustainability-oriented performance in Islamic microfinance institutions.